Double feature selection algorithm based on low-rank sparse non-negative matrix factorization - Shang, Ronghua; Song, Jiuzheng; Jiao, Licheng; Li, Yangyang (International journal of machine learning and cybernetics, 2020)
Recently, many feature selection algorithms based on non-negative matrix factorization have been proposed. However, many of these algorithms only consider unilateral information about global or local geometric structure normally. To this end, this paper proposes a new feature selection algorithm called double feature selection algorithm based on low-rank sparse non-negative matrix factorization (NMF-LRSR). Firstly, to reduce the dimensions effectively, NMF-LRSR uses non-negative matrix factorization as the framework to further reduce the dimension of the feature selection which is originally a dimension reduction problem. Secondly, the low-rank sparse representation with the self-representation is used to construct the graph, so both the global and intrinsic geometric structure information of the data could be taken into account in the process of feature selection, which makes full use of the information and makes the feature selection more accurate. In addition, the double feature selection theory is used to this paper, which makes the result of feature selection more accurate. NMF-LRSR is tested on the baseline and the other six algorithms in the literature and evaluated them on 11 publicly available benchmark datasets. Experimental results show that NMF-LRSR is more effective than the other six feature selection algorithms.